2005
DOI: 10.1111/j.1533-8525.2005.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Minority Concentration, Disadvantage, and Inequality in The Nonmetropolitan United States

Abstract: The implications of the residential concentration of minority populations are issues of vital concern in the United States. Much of the previous minority concentration literature has focused on African-American residents of metropolitan communities. This article expands on this literature by exploring a variety of minority groups in nonmetropolitan communities. It was found that the minority residents of communities with large minority populations were in worse socioeconomic conditions than the minority reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 34 publications
2
41
0
2
Order By: Relevance
“…Indeed, nearly five decades of research on the ''visibility-discrimination'' hypothesis has consistently shown that racial subordination and inequality are exacerbated whenever the minority population is large, visible, and potentially threatening to whites (e.g., Albrecht, Albrecht, and Murguia 2005;Beggs, Villemez, and Arnold 1997;Blalock 1956;Brown and Fuguitt 1972;Glenn 1964). There is much less agreement about the causes of this statistical association.…”
Section: The Present Studymentioning
confidence: 95%
“…Indeed, nearly five decades of research on the ''visibility-discrimination'' hypothesis has consistently shown that racial subordination and inequality are exacerbated whenever the minority population is large, visible, and potentially threatening to whites (e.g., Albrecht, Albrecht, and Murguia 2005;Beggs, Villemez, and Arnold 1997;Blalock 1956;Brown and Fuguitt 1972;Glenn 1964). There is much less agreement about the causes of this statistical association.…”
Section: The Present Studymentioning
confidence: 95%
“…Relative to minority workers, the income gap between white and minority populations remains large even after decades of legislative and policy efforts. Further, an extensive literature has found that the gap between white and minority incomes is greatest where minority populations are largest (Albrecht et al 2005;Cohen 1998;Fossett and Seibert 1997;Frisbie and Neidert 1977;McCreary et al 1989;Wilcox and Roof 1978).…”
Section: Social Conditions and Inequalitymentioning
confidence: 97%
“…The percent of the population that is minority is another factor expected to be related to economic structure, the educational income gap, and overall income inequality. A long line of social science research has found that inequality levels tend to be greater where the size of the minority population is larger (Albrecht et al 2005;Cohen 1998;Fossett and Seibert 1997;Frisbie and Neidert 1977;McCreary et al 1989;Wilcox and Roof 1978). Not only do minority populations tend to have lower incomes and lower levels of education, but research shows that white incomes are often higher in communities where minority populations are extensive, perhaps because the advantaged can exploit low-income, minority populations (Albrecht et al 2005).…”
Section: Economic Structure Region Moderating Variables and Educatmentioning
confidence: 96%